The Relationship between Advertising, Archetypal Imaginaries and Myths - Elena OPRAN (Social Sciences and Education Research Review, 2025)
This paper aims to demonstrate that mythical structures, capable of organizing the imaginary and directing it toward acquiring products as symbolic objects, play a significant role in advertising design. By extension, they leave an imprint on the broader cultural and mental landscape of the contemporary world. The relationship between archetypes and myths is outlined as a complex interplay of actualization, manifestation, and organization through which the two intertwine. As a secular form of contemporary remythologization, advertising borrows numerous iconic schemes and a symbolic polysemy from the archetypal reservoir to transfer them into the realm of brands and products.